Quantum coherence phenomenon in disordered Bi2SeTe2 topological single crystal: effect of annealing. (24th March 2017) - Amaladass, E P; Devidas, T R; Sharma, Shilpam; Mani, Awadhesh
Abstract: We report a comparative magnetotransport study on pristine and annealed Bi2 SeTe2 single crystals. The pristine sample shows a metallic trend from 300 to 180 K, and an insulating behavior for T   <  180 K, whereas the annealed sample exhibits an insulating nature in the entire 4.2–300 K temperature range. Magnetoresistance (MR) of pristine and annealed samples reveals contrasting behaviour as a function of temperature ( T ) and magnetic field ( B ). At 4.2 K, the pristine sample shows weak antilocalization (WAL) behavior at low fields and transforms to weak localization (WL) behavior (negative MR) for B   >  2.5 T. Further, the quantum MR behaviours seen at low temperature gradually transform to classical B 2 dependent upon increasing the temperatures. In contrast, the annealed sample shows a WAL at small field superimposed on a parabolic feature for B   >  ±4 T at low temperatures ( T   <  20 K). It shows a linear MR at intermediate temperatures (40 K  <   T   <  100 K) and a parabolic MR at temperatures T   >  100 K. Hall measurements on both samples exhibit a nonlinear behavior at 4.2 K pointing to the existence of two types of carriers with different mobility. The annealed sample also shows a drastic decrease in mobility by one order of magnitude and a reduction in Ioffe–Regel parameter ( k F l ) by a factor of ~3. Disorder-induced localization of bulk carriers and its coexistence with localization-immune surface carriers at low T leads to WAL and WL. MR observed in the annealed sample can be attributed to the presence of both quantum–classical contribution and has been analysed using the Hikami–Larkin–Nagaoka (HLN) equation.